Does Consumption-Wealth Ratio Signal Stock Returns? VECM Results for Germany - Fang Xu (Kiel University, Department of Economics, 2005)
This paper studies the signalling effect of the consumption-wealth ratio (cay) on German stock returns via vector error correction models (VECMs). The effect of cay on U.S. stock returns has been recently confirmed by Lettau and Ludvigson with a two-stage method. In this paper, performances of the VECMs and the two-stage method are compared in both German and U.S. data sets. It is found that the VECMs are more suitable to study the effect of cay on stock returns than the two-stage method. Using the Conditional-Subset VECM, cay signals real stock returns and excess returns in both data sets significantly. The estimated coefficient on cay for stock returns turns out to be two times greater in U.S. data than in German data. When the two-stage method is used, cay has no significant effect on German stock returns. Besides, it is also found that cay signals German wealth growth and U.S. income growth significantly.
Keywords: G10; C32; 330; stock returns; consumption-wealth ratio; VECM; Kapitalertrag; Erwartungstheorie; Prognoseverfahren; Gesamtwirtschaftlicher Konsum; Vermögen; Einkommen; Theorie; Fehlerkorrekturmodell; Schätzung; Vereinigte Staaten; Deutschland